Effects of 60Co gamma radiation on crotamine - Boni-Mitake, M.; Costa, H.; Spencer, P. J.; Vassilieff, V. S. [UNESP]; Rogero, J. R. (Associação Brasileira de Divulgação Científica (ABRADIC), 2001)
Ionizing radiation can change the molecular structure and affect the biological properties of biomolecules. This has been employed to attenuate animal toxins. Crotamine is a strongly basic polypeptide (pI 10.3) from Crotalus durissus terrificus venom composed of 42 amino acid residues. It induces skeletal muscle spasms leading to a spastic paralysis of hind limbs in mice. The objective of the present study was to carry out a biochemical study and a toxic activity assay on native and irradiated crotamine. Crotamine was purified from C.d. terrificus venom by Sephadex G-100 gel filtration followed by ion-exchange chromatography, and irradiated at 2 mg/ml in 0.15 M NaCl with 2.0 kGy gamma radiation emitted by a 60Co source. The native and irradiated toxins were evaluated in terms of structure and toxic activity (LD50). Irradiation did not change the protein concentration, the electrophoretic profile or the primary structure of the protein although differences were shown by spectroscopic techniques. Gamma radiation reduced crotamine toxicity by 48.3%, but did not eliminate it.
Keywords: crotamine; gamma radiation; chromatography; toxicity; circular dichroism